PREVALENCE, PATTERN, AND PREDICTORS OF PREMENSTRUAL SYNDROME AND PREMENSTRUAL DYSPHORIC DISORDER AMONG COLLEGE GIRLS - K V, LISHA GOVIND; V K, CHELLAMMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Premenstrual syndrome (PMS) occurs 7–14 days before the onset of menstruation and subsides with the commencement of menstrual flow, affects women during their reproductive age, and is associated with physical, psychological, and behavioral changes. If the mental symptoms predominate are very severe and are associated with impairment, then the patient is classified as having premenstrual dysphoric disorder (PMDD) which may be viewed as a severe subtype of PMS. This can interfere with the lives of the affected, as well as their interpersonal relationships. Methods: This study was conducted at KMCT medical college from November 2021 to May 2022. An awareness program which was informative and well-interacted was conducted for each batch of students regarding the various aspects of this disorder before screening for this study. Premenstrual symptoms screening tool (PSST) was used to screen students for the presence of disturbing symptoms. They were asked to write down the various ways that they deal with these menacing symptoms in a separate form. Institution ethics committee approval was taken to carry out this study. PSST it is the screening tool developed by Steiner et al. Results: A total of 318 students from all batches of college took part in this study actively. On screening by PSST, 44 students qualified for PMDD, 89 students met the criteria for PMS, and the remaining 185 had no to mild premenstrual symptoms (Table 1). Among the 89 students in premenstrual symptoms group, most common symptoms reported were anger/irritability −66%, fatigue/lack of energy −45%, and difficulty concentrating −45%. In 44 students who had qualified for PMDD, 84% reported anger/irritability, 81% reported tearful/increased sensitivity, and 75% reported anxiety/ tension followed by depressed mood in 73%. Conclusion: PMS and PMDD are prevalent among substantial proportion of college girls with significant negative influence on academic performance, emotional well–being, and behavior. The pattern of premenstrual symptomatology is different between PMS, PMDD, and in overall college students. The predictors of PMS and PMDD are age, education, heavy menstrual flow, dysmenorrhea, and family history of PMS. The knowledge and health seeking behavior of college students toward PMD are quite low. Strategies should be drawn and implemented for timely recognition and management of PMS and PMDD in college girls.